Effect of two-step austempering heat treatment on the dry sliding wear behavior of austempered ductile cast iron - Bello, Kamilu Adeyemi; Dodo, Rayyan Mamuda; Babaswasun, Muhammad Sani; Umma, Abdullahi; Adebisi, Abdulmumin Adetayo; Maleque, Md. Abdul (Nigerian Metallurgical Society (NMS), 2022)
The study targeted the impact of two-step austempering heat treatment on the tribological (wear and friction) properties of austempered ductile cast iron (ADI). Wear samples were prepared from ductile cast iron in accordance with ASTM standards. Afterwards, samples treated with two different austempering heat treatments; conventional and two-step austempering treatments (step-up and step-down schemes). The conventional austempering treatment was conducted by austenitizing as-cast samples at 927oC and then austempered at 400 oC. In the event of step-up austempering treatment, the as-cast samples were austenized at 927oC, initially austempered at 250, 300 and 350 oC followed by second austempering at 400 oC for each sample. However, samples were austenized at 927oC, first austempered at 400 oC and then austempered again between 250 and 350 oC for step-down treatment scheme. Wear and co-efficient of friction for as-cast and ADI samples were evaluated using ball-on-disc tribometer machine. Additionally, microstructures of the as-cast and ADI samples as well as the worn surface morphologies of the samples were also examined using optical microscopy. The result indicated that the latter austempering heat treatment demonstrated lesser wear rate and co-efficient of friction as compared to the as-cast and conventional ADI samples. Furthermore, two-step austempering treatment conducted at 300 oC for both step-up and step-down exhibited optimum wear resistance and low friction, which could be attributed to the finer ausferritic structure obtained in this condition. Thus, the results of this finding indicate that two-step austempering treatment successfully enhanced wear and friction properties of as cast ductile cast iron.